Studi Putusan Mahkamah Konstitusi Nomor 114/PUU-XX/2022 Terhadap Eksistensi Sistem Proporsional Terbuka Sebagai Identitas Demokrasi Di Indonesia - Paisal Abdi; Insan Tajali Nur; Rosmini (Jurnal Ilmu Hukum, 2024)
This research was carried out in order to conduct an assessment of the Constitutional Court decision number 114/PUU-XX/2022 regarding the existence of an open proportional system as the identity of democracy in Indonesia. As is known, the decision rejected the review of several articles in the law relating to the open proportional system ( Law Number 7 of 2017 concerning General Elections) so the implication is that the open proportional system is still used as a mechanism for the general election system in Indonesia. As well as looking from another perspective regarding the advantages and disadvantages of the proportional system itself, the history of the application of open and closed proportional systems in Indonesia in the implementation of general elections, why the open proportional system was stated by constitutional judges as the ideal system to be implemented in Indonesia, and seeing how consistent the judges are constitution in deciding cases related to the open proportional system by comparing several constitutional court decisions related to the open proportional system. The author uses a doctrinal (normative juridical) approach. Research carries out analysis and research based on expert opinions and related theories in conducting discussions. Thus creating a correlation which thus sees the conclusion drawn by the constitutional judges that the open proportional system is the ideal system to be applied in general elections in Indonesia and that the existence of the open proportional system as a system in general elections in Indonesia is increasingly strengthened.